DropletMicroarray: facile formation of arrays of microdroplets and hydrogel micropads for cell screening applications - Boles, Erica Ann; Geyer, Florian Ludwig; Nedashkivska, Victoria; Levkin, Pavel (Lab on a chip, 2012)
We describe a one-step method for creating thousands of isolated pico- to microliter-sized droplets with defined geometry and volume. Arrays of droplets are instantly formed as liquid moves along a superhydrophilic-superhydrophobic patterned surface. Bioactive molecules, nonadherent cells, or microorganisms can be trapped in the fully isolated microdroplets for high-throughput screening, or in hydrogel micropads for screening in 3D microenvironments.
Gesehen am 24.09.2018